Pendampingan Ibu Hamil Dalam Pencegahan Kek Di Kelurahan Bugis Kabuapaten Sumbawa - Hamdin hamdin; Herni Hasifah (Jurnal Pengabdian Ilmu Kesehatan, 2023)
Abstract Maternal health is one of the main keys for the health of the next generation, while children's health is a future national asset (Hogan et al, 2010). Indonesia has not shown significant progress in efforts to reduce maternal and child mortality (Ministry of Health RI, 2010). One of the reasons for the high MMR is anemia in pregnancy. Pregnant women and toddlers are a vulnerable group to health problems and malnutrition. Based on the 2013 Nutrition Adequacy Rate (RDA), the purpose of this community service activity is to screen mothers with chronic energy deficiencies (KEK). The benefit of this activity is that pregnant women can find out their upper arm circumference (LILA) (SEZ status). That way pregnant women can increase their food consumption pattern to be diverse, nutritious, balanced and safe (B3A) by utilizing local food. Conclusion During pregnancy, pregnant women must meet nutritional needs for themselves and for the growth and development of the fetus because fetal nutrition depends on maternal nutrition.